2018 IEEE 12th International Conference on Semantic Computing (ICSC) 2018
DOI: 10.1109/icsc.2018.00029
|View full text |Cite
|
Sign up to set email alerts
|

Support Vector Machine Active Learning Algorithms with Query-by-Committee Versus Closest-to-Hyperplane Selection

Abstract: This paper investigates and evaluates support vector machine active learning algorithms for use with imbalanced datasets, which commonly arise in many applications such as information extraction applications. Algorithms based on closestto-hyperplane selection and query-by-committee selection are combined with methods for addressing imbalance such as positive amplification based on prevalence statistics from initial random samples. Three algorithms (ClosestPA, QBagPA, and QBoostPA) are presented and carefully e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…to the separating hyper-plane is an indicator of uncertainty, with the example having the lowest distance being most uncertain [83].…”
Section: Positive Certain and Uncertainmentioning
confidence: 99%
“…to the separating hyper-plane is an indicator of uncertainty, with the example having the lowest distance being most uncertain [83].…”
Section: Positive Certain and Uncertainmentioning
confidence: 99%
“…We also use the closest-to-hyperplane selection algorithm with SVM for active learning [35], [36], [16]. This is because previous work has shown that it has better performance over other selection algorithms used [37]. For each iteration of training, the number of samples used is determined by a batch percent, bp.…”
Section: A Iterative Learning Setupmentioning
confidence: 99%
“…We take advantage of that body of research to select our set of experimental approaches, which include sample selection via Gaussian mixture models [17], [31] and Determinantal Point Processes (DPPs) [38], which have proven effective in modeling diversity [21], [76]. Using supervised learners as the active learning techniques [5], [66] are not suitable for our current study since we concentrate on building a language model without prior knowledge [35].…”
Section: Related Workmentioning
confidence: 99%